Late glacial and postglacial climatic variation in the Near East - Butzer, Karl W. (ERDKUNDE, 1957)
The author attempts to reconstruct the climate fluctuations since the last ice age for a part of the subtropical latitudes, the Near East. Relatively useful results are available for this area, even if they do not reach the same level of accuracy as in higher latitudes, since pollen analysis cannot be used here. On the basis of stratigraphic, morphological, archaeological and historical findings, the following periods can be separated: 1. Postpluvial 1 (following the last pluvial period). Drier and a little cooler than today with pronounced wind erosion. High point probably in the 11th century. v. 2. Subpluvial I (probably in the 9th century AD). Fairly humid with rainfall ranging about halfway between that of a pluvial and that of modern times. Lower temperatures with a final push from the small Würm cirque glaciers in the highlands. 3. Postpluvial IIa (ca. 8000-6500 BC). Again drier than today and apparently warmer than during the previous phase. 4. Postpluvial IIb (ca. 6500-5500 or 5000 BC). Slightly wetter, similar to current climate. 5. Subpluvial II (ca. 5000-2400 BC). This second post-pluvial wet period can be compared to Subpluvial I in terms of its intensity, but lasted longer and, together with the following period, was characterized by somewhat greater warmth (climate optimum!). Short-term reductions in precipitation just before and just after 4000 and around 3000 BC. BC stand out. 6. Postpluvial III (2400-850 BC). After a sudden change in climate, arid conditions — with temperatures similar to those before — reappear. A wetter interval can be determined at least once (in the 12th century). 7. Postpluvial IVa (850 BC-700 AD). Broadly the same as today's climate, just a little drier with slightly warmer winters. Of note is a pronounced drought about AD 590-645. 8. Postpluvial IVb (Since AD 700). From about AD 650 an increasing number of colder winters are noticeable, especially during the early Islamic period. The interval AD 700-1000, and the late 13th, early 15th, and early 17th centuries. were relatively wet. The 12th century. a little drier. Since 1900 there has been a noticeable decrease in precipitation of perhaps 10-15%, which appears to be related to the recent climatic fluctuation. Small local temperature increases are present, but should not be generalized for the Near East. Since about 1938, however, there have been signs of a renewed turn to slightly wetter conditions.